Adverse Drug Reactions in Pediatric Oncohematology: A Systematic Review - Amaro-Hosey, Kristopher; Danés, Immaculada; Agustí, Antònia (Frontiers in Pharmacology, 2022)
Introduction: Adverse drug reactions (ADR) are an important cause of morbidity and mortality in pediatric patients. Due to the disease severity and chemotherapy safety profile, oncologic patients are at higher risk of ADR. However, there is little evidence on pharmacovigilance studies evaluating drug safety in this specific population. Methods: In order to assess the incidence and characteristics of ADR in pediatric patients with oncohematogical diseases and the methodology used in the studies, a systematic review was carried out using both free search and a combination of MeSH terms. Data extraction and critical appraisal was performed independently using a predefined form. Results: Fourteen studies were included, of which eight were prospective and half focused in inpatients. Sample size and study duration varied widely. Different methods of ADR identification were detected, used alone or combined. Causality and severity were assessed frequently, whereas preventability was lacking in most studies. ADR incidence varied between 14.4% to 67% in inpatients, and 19.6% to 68.1% in admissions, mainly in the form of hematological, gastrointestinal and skin toxicity. Between 11 to 16.5% ADR were considered severe, and preventability ranged from 0% to 74.5%. Conclusions: ADR in oncohematology pediatric patients are frequent. A high variability in study design and results has been found. The use of methodological standards and preventability assessment should be reinforced in order to allow results comparison between studies and centers, and to detected areas of improvement.